Pengolahan Dan Pemasaran Online Produk Susu Kefir Di Desa Gunung Perak Kabupaten Sinjai - Hadrianti H.D Lasari; Safaruddin Safaruddin; Ka’bah Ka’bah (Lembaga Layanan Pendidikan Tinggi Wilayah IX Sulawesi, 2019)
The potential of this agribusiness can be found and developed in Gunung Perak Village. In the village fresh milk is produced which is then processed in the Sintari Dairy Cooperative, better known as Susin. Aiming at product innovation, the community service team conducted this Community Service Activity smoothly for five months. Participants in this activity generally work as teaching teachers, housewives and farmers. This activity is dominated by participants aged 18-45 years and 100% participants are female. This activity was also followed by PKK in Gunung Perak Village. Mc Nemar X2 test with a Significant value of 0.007 <0.05 so that there are differences in knowledge before and after exposure to material about Processing and Online Marketing of Kefir Dairy Products in Gunung Perak Village, West Sinjai District, Sinjai District. This activity, public knowledge increased by an average value difference of 1.88 with the addition of knowledge reaching 9.4%.